Manjarix attenuated pain and joint swelling in a rat model of monosodium iodoacetate-induced osteoarthritis. Issue 9 (25th August 2020) - Abdel-Rahman, Rehab F.; Abd-Elsalam, Reham M.; Amer, Mohammed S.; EL-Desoky, Ahmed M.; Mohamed, Shanaz O.
Abstract : Manjarix significantly reduced both the knee joint swelling and the pathological injury of the joints, with no evidence of osteo-reactivity in the radiographic examination. Manjarix also significantly prevented MIA-induced pain behavior. Abstract : Osteoarthritis (OA) is a joint disease characterized by degeneration of cartilage, intra-articular inflammation, remodeling of subchondral bone and joint pain. The present study was designed to assess the therapeutic effects and the possible underlying mechanism of action of Manjarix, a herbal combination composed of ginger and turmeric powder extracts, on chemically induced osteoarthritis in rats. An OA model was generated by intra-articular injection of 50 μL (40 mg mL −1 ) of monosodium iodoacetate (MIA) into the right knee joint of rats. After one week of osteoarthritis induction, a comparison of the anti-inflammatory efficacy of indomethacin at an oral dose of 2 mg kg −1 daily for 4 successive weeks versus five decremental dose levels of Manjarix (1000, 500, 250, 125, and 62.5 mg kg −1 ) was performed. Serum inflammatory cytokines, interleukin 6, interleukin 8, and tumor necrosis factor alpha; C-telopeptide of type II collagen (CTX-II) and hyaluronic acid (HA) were measured, along with weekly assessment of the knee joint swelling. Pain-like behavior was assessed and knee radiographic and histological examination were performed to understand the extent of pain due to cartilage degradation. Manjarix significantly reduced the knee joint swelling, decreased the serum levels of IL6, TNF-α, CTX-II and HA, and reduced the pathological injury in joints, with no evidence of osteo-reactivity in the radiographic examination. Manjarix also significantly prevented MIA-induced pain behavior. These results demonstrate that Manjarix exhibits chondroprotective effects and can inhibit the OA pain induced by MIA, and thus it can be used as a potential therapeutic product for OA.